(untitled) (Bangladesh Journal of Neuroscience, 2013)
Neurological features of severe hypoglycemia range from reversible focal deficits to irreversible coma or death. Diffusion weighted MRI of brain image is a useful tool in evaluating profound hypoglycemic brain injuries. We report a case of 27 year old male who died from brain injuries following an episode of prolonged hypoglycemia. We here discuss the neuropathological and diffusion-MRI changes of hypoglycemic brain injuries and its prognostic importance. Bangladesh Journal of Neuroscience 2013; Vol. 29 (1) : 60-63